Novel Variant of SLC34A3 in a Compound Heterozygous Brazilian Girl with Hereditary Hypophosphatemic Rickets with Hypercalciuria - Luciana Pinto Valadares; Daniel Rocha de Carvalho (JCRPE)
Hereditary hypophosphatemic rickets with hypercalciuria (HHRH) is a rare fibroblast growth factor-23-independent disorder caused by biallelic variants in the SLC34A3 gene. The disease severity varies, and patients have an increased risk of developing renal complications. Phosphate supplementation is the standard of care and active vitamin D analogs are not indicated as they could worsen the hypercalciuria. We report a Brazilian girl with HHRH who presented with knee pain and progressive genu valgum deformity that became apparent from the age of eight years onwards. Nephrocalcinosis was also identified at age 13 years. Targeted next-generation sequencing for hereditary forms of rickets detected compound heterozygous pathogenic variants in SLC34A3, including a novel missense variant c.1217G>T (p.Gly406Val). Compliance to oral phosphorus therapy was suboptimal and adjunctive chlorthalidone therapy improved hypercalciuria. This report highlights the phenotypic variability and also expands the list of SLC34A3 variants associated with HHRH. An accurate diagnosis is key for optimal treatment. Of note, thiazide diuretics may be useful as adjunctive therapy for controlling hypercalciuria.